Biogenic propane production by a marine Photobacterium strain isolated from the Western English Channel - Currie, Felicity; Twigg, Matthew S.; Huddleson, Nicholas; Simons, Keith E.; Marchant, Roger; Banat, Ibrahim M. (Frontiers in Microbiology, 2022)
Propane is a major component of liquefied petroleum gas, a major energy source for off-grid communities and industry. The replacement of fossil fuel-derived propane with more sustainably derived propane is of industrial interest. One potential production route is through microbial fermentation. Here we report, for the first time, the isolation of a marine bacterium from sediment capable of natural propane biosynthesis. Propane production, both in mixed microbial cultures generated from marine sediment and in bacterial monocultures was detected and quantified by gas chromatography–flame ionization detection. Using DNA sequencing of multiple reference genes, the bacterium was shown to belong to the genus Photobacterium. We postulate that propane biosynthesis is achieved through inorganic carbonate assimilation systems. The discovery of this strain may facilitate synthetic biology routes for industrial scale production of propane via microbial fermentation.